Genetics of Some Wool Traits in Sheep: A Review - Olympica Sarma; Mubashir Ali Rather; Shivangi Maurya (Archives of Current Research International, 2024)
Greasy fleece yield, staple length and fibre diameter are complex quantitative traits influenced by various genetic and environmental factors. Among non-genetic factors year of birth, gender of lamb, centre of rearing, parity and type of birth are known to influence wool traits in different sheep genetic resources. To develop effective breeding objectives and accurately evaluate genetic potential, more precise analysis of genetic parameters and correlations between growth traits is essential. However, inconsistent results were observed across breeds and studies, highlighting the need for breed-specific optimization strategies. Greasy fleece yield, fibre diameter and staple length are critical determinants of wool quality and quantity. Wool traits are moderately (20–50%) to highly heritable (≥50%), so improving quality and quantity of a wool clip can happen even after one generation. The significant variations observed among breeds underscore the need for breed-specific optimization strategies. By integrating genetic and environmental factors, sheep breeders and producers can develop effective breeding programs, improve wool production, and enhance profitability. Wool traits are moderately to highly heritable, however, very low and very high estimates have also been reported in different sheep genetic resources. The heritability estimates correspond to the genetic variation in a trait. Gene mapping has identified chromosomal regions influencing fibre quality and production, enabling more efficient selection of superior wool production. Recent studies have employed various techniques to investigate the impact of fibre-related genes, including the candidate gene approach, transcriptome analysis and genome-wide association studies. It is concluded that wool traits being quantitative in nature are governed by different genes and are influenced by genetic and different environmental factors.